Subjetividade e religião no pensamento de Kierkegaard - Massarollo Junior, Leosir Santin (2012)
The following study aims to investigate the influence of religion and subjectivity in the core of Søren A. Kierkegaard philosophical conception, mainly in the works Frygt og baeven (1843) (Fear and Trembling); Begrebet Angest (1844) (The Concept of Dread) and Sygdommen till doeden (1849) (The Sickness Unto Death). The Danish philosopher relies on concepts of faith / sin and objectivity / subjectivity to clarify his positions; in his analysis and conclusions it can be observed the direct influence of Ethics and Psychology, since it is an investigation about myself . Kierkegaard, from synthesis of what the individual is and its relations with harmony s divinity, in such relationship, the author affirms the existence as a constant process of edification. This process, inherent in the act of being, will have its analysis in Ethics and Psychology, but it will be fully expressed only in the subjectivity inclined to religious; which makes the Dogam, in many cases, the base of Kierkegaard investigation. Because it is a synthesis of the finite and infinite, temporal and eternal, freedom and necessity, dialectical myself radiates both finite infinity. This nature of man transcends the objective analysis, conducting the investigation in meanders in which the Dogmatic should match the "mechanism" of assessment. Having as modus aprendi the individualization, since Dogam demands isolation, the existence philosophy relies on its own developments to the edification of myself . With this conception, the individual is understood as a more elevated category from Kierkegaard s thoughts. This will result in the mutual abandon of systems and crowds, because in retirement, according to the Danish philosopher, the individual learns something that any science can teach: the edification. This will constitute in the comprehension and acceptance of the existence that allows the areas of life, initializing with Ethics and going forward with Dogam. The methodology used has as purpose, ultimately, the analysis of the inner from subjective reactions capable of expose the tension of existence, such as the desperation, interiority, faith, sin and others. The submission or elevation of the men will be constant observed in Kierkegaard s investigations. With this notion, the individual establishes alone the edification progress, guiding in its reality in the conditioned divinity synthesis. A path is open to the individuality as herald of the truth, as unrestricted statement and love for life. To achieve this statement, Kierkegaard has the faith as the last human passion, capable of conducting the synthesis and sublimate its concerns. In this sense, we can understand the philosophy proposed by Kierkegaard as a return do the myself in its deep religious implications.